Pendidikan akidah akhlak dalam pembentukan karakter peserta didik Madrasah Ibtidaiyah (Studi Kasus Pada Peserta Didik Kelas Tinggi MI Nagrog Desa Padasuka Kecamatan Sukarame Kabupaten Tasikmalaya) - Mahmudin, Wildan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2023)
This issue was raised based on the values of the nation's character which is the pillar of education and the demands of the National Education System Law Number 20 of 2003 article 3 that to develop the potential of students to become complete Indonesian people, namely having faith and devotion to God Almighty, having knowledge and skills, noble ethics, physically and spiritually healthy, having a steady personality, Smart, creative, independent and have a sense of responsibility. One of the roles in character education is the moral creed teacher, because this is related to the moral aspects of students. The purpose of this study is to determine the character of students through moral creed education and the implementation of moral creed education in MI Nagrog. The method used in research is qualitative method. The subjects of this study include principals, teachers and high-class students, namely grades 4, 5 and 6. The data sources used in this study were interviews, questionnaires, observations, and documentation. This study concluded that the character of students in MI Nagrog was good enough because students had performed congregational dhuhr prayers, dzuha prayers, tadarus, threw garbage in its place, gave praise to friends who had participated in competitions, carried out daily picket tasks, Get used to being present on time, and get used to speaking in polite language, as a form of religious character, responsibility, discipline, independence, honesty, respect for achievements, care for the environment, and courtesy.